Hubungan Frekuensi Menoton TV Pada Anak SD(Kelas V) Dengan Tingkat Prestasi Belajar Anak Usia 10-11 Tahun - Erna Susilowati; SITI MUSYAROFAH (Akademi Keperawatan Dharma Husada Kediri, 2016)
Television is feeling important to children. Frequency ang long of watching TV to children’s is higher then they are learn frequency. It’s means in sociality process they will influenced with TV program’s. Objective direction of this scientific work is to know relation between frequency of watching TV to elementary student’s ( class V) and learn achievement in child 10-11 years old. Desain that we using is correlation with cross sectional metode. The sample in elementary student’s class V in SDN Drenges II kertosono. Total sampling 13 student’s. We use systemic observation to gathering data and analys with pearson’s coefisien correlation and interval correlation value. Result that we get in scientific work is r:0,1, that’s mean frequency of watcing TV and leanring achivment have positif relatioan and the table of coefisien correlation 0,00<KK<=0,20 having weak relation. We can say that frequency of watching TV and learn achivment hava relation., but many another factor can be influenced children achivment. Like children’s IQ, environment and learning tool’s. so we must can be arrange of time to children to learn and play. Paretnt’s role is too important for supporting chid. Key’s word: Television, learn achivment, children